PV array reconfiguration with electrical energy storage system for power system frequency regulation - Zhou, Jun; Liu, Chong; Li, Kun (Frontiers in Energy Research, 2022)
In this work, a novel PV station participating FR technique based on PV array reconfiguration and battery energy storage system (BESS) is put forward. Two conflicting targets are considered, i.e., maximizing the profit of PV station and minimizing power deviation of FR signals. In order to two conflicting goals simultaneously, multi-objective golden eagle optimizer (MOGEO) and improved ideal point decision making method are applied. MOGEO is a nature-inspired swarm-based metaheuristic for solving multi-objective optimization problems. MOGEO mimics the behavior of golden eagles in tuning speed at different stages of their spiral trajectory for hunting. Two cases are designed and tested. Therefore, the simulation results verify that the proposed method contributes to the frequency response of PV station.